Human resource management and Army recruiting : analyses of policy options - Dertouzos, James N., 1950- (Rand Corporation monograph series., 2006)
U.S. Army Recruiting Command (USAREC) is faced with the challenge of ensuring that the flow of qualified volunteers is adequate to meet future active-duty accession requirements. This report documents research methods, findings, and policy conclusions from a project analyzing human resource management options for improving recruiting production. It details research designed to develop new insights to help guide future recruiter management policies. The research involves econometric analyses of three large and rich datasets. The first analysis compares the career paths of enlisted personnel, including recruiters. The second analyzes individual recruiter characteristics and links those characteristics with their productivity, controlling for a variety of independent factors. Finally, the research focuses on station-level recruiting outcomes, paying close attention to the management options that can affect recruiter production and effort. These empirical analyses demonstrate that various types of human resource management policies can be very helpful in meeting the Army's ambitious recruiting requirements. For example, the findings have implications for human resource policies in the areas of selecting soldiers for recruiting duty, assigning recruiters to stations, missioning to promote equity across recruiters, missioning to increase recruiter productivity, using promotions to motivate and reward recruiters, and screening out recruiters who are under-producing. Although the gains from any individual policy appear to be modest, the cumulative benefits of implementing multiple policies can save the Army hundreds of millions of dollars annually. This work will interest those involved in the day-to-day management of recruiting resources as well as researchers and analysts engaged in analyses of military.